REVOLUTION OF MENTAL IN THE PERSPECTIVE OF PANCASILA EDUCATION - Alif Lukmanul Hakim; Wahyu Dwi Yulianto (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2021)
Revolution of Mental in The Perspective of Pancasila Education. This scientific writing merely aims to study further the meaning of mental revolution existing in Indonesia as one of such either program or what later is called national movement in order for the nation itself to generate the nation’s next generation possessing the great and real character of Pancasila. To say more, the study of mental revolution also has an objective or goal for the youth to be able to compete and face actively the change of the global world characteristically based on Pancasila perspective. This study takes the critical view of the young generation who shows almost little or no respect to the application of the value of Pancasila in their daily. In other words, the jubilee tends to ignore the moral value of behavior  containing Pancasila. The study then applies the qualitative methode through the study of literature which is then processed using descriptive analysis. This qualitative study furthermore derives the analysis of mental revolution from the perspective of Pancasila education: background, process, and goal of mental revolution itself. To conclude as the last point, it is obtained that the meaning of Pancasika education exceeds the meaning of mental revolution itself, which means thay mental revolution is merely one of such many aspects learnt from the education of Pancasila